Feasibility of establishing the origin designation system of food products in Costa Rica - Granados, Leonardo (2002)
Based on the opinion of people involved in rural development and associated with the food and agriculture sectors, the possibility to establish in Costa Rica the origin designation system was evaluated, as a means to add more value and promote those agricultural and traditional food products with a well-known geographical origin. The people surveyed showed little knowledge about the subject. However, a highly positive reception was perceived not only for this type of products but also for the possibility of establishing the system in Costa Rica; according yo those consulted, it will improve the quality and image of the products and enhance the chances for new markets to open. The most important limiting factor mentioned against the establishment of the origin designation system was the lack of knowledge and experience about the system. Therefore, it was recommended to carry out more research about the products that show potential to be included in the system, and to develop an institutional framework for the system to operate.